Novel color M-mode echocardiography for non-invasive assessment of the intraventricular pressure in goats: Feasibility, repeatability, and the effect of sedation - Mandour, Ahmed S.; Samir, Haney; Yoshida, Tomohiko; Matsuura, Katsuhiro; Hamabe, Lina; Shimada, Kazumi; Abdelmageed, Hend A.; Elbadawy, Mohamed; Uemura, Akiko; Takahashi, Ken; Watanabe, Gen; Tanaka, Ryou (Frontiers in Veterinary Science, 2022)
Background The intraventricular pressure difference and gradients (IVPD and IVPG), estimated from color M-mode echocardiography (CMME) of the transmitral flow, have been established as novel indices for the evaluation of heart functions. Until now, no study demonstrates the feasibility of the new approach in any farm animals. This study aims to assess the feasibility and repeatability of CMME-derived IVPD and IVPG variables in goats and explore the effect of sedation. Material and methods Sixteen male Shiba goats were included and underwent conventional echocardiography. Eight goats were used in the repeatability of IVPD/IVPG variables. Another eight goats were used to examine the effect of sedation on IVPD/IVPG measurements. CMME between the base and apex of the left ventricle was carried out. The IVPD and IVPG were analyzed using in-house code software (MATLAB). Data analysis was carried out for the imaging quality score (IQS), analysis score, repeatability, variability, intraclass correlation coefficient (ICC), and the effect size (biserial ranked correlation, rc) of sedation on the measured variables. Results CMME was achieved in all goats and enabled the measurement of IVPD and IVPG. The IQS from all goats was acceptable. The IVPD and IVPG were expressed as total, basal, mid-to-apical, mid, and apical parts. Low to moderate variability was observed on the obtained measurements (coefficient of variation CV 95% <25%) except for the apical segment. The IVPD/IVPG measurements were repeatable and showed neither significant effect of goat nor time as well as the interaction between them. The overall ICC was higher than 0.75 in all variables except for apical IVPD and apical IVPG. Xylazine administration reduced the total, basal and mid parts of both IVPD and IVPG with a large effect size (rc: 1.0, 0.889, 1.0 in IVPD; 0.944, 1.0, 1.0 in IVPG). Conclusion Assessment of IVPD and IVPG from CMME is repeatable in goats and can be used in further cardiovascular research in farm animals concerning the pathophysiology and pharmacological studies.